2020
DOI: 10.1002/jcd.21712
|View full text |Cite
|
Sign up to set email alerts
|

Colourings of star systems

Abstract: An e-star is a complete bipartite graph K e 1, . An e-star system of order n S n > 1, ( )chromatic number, colouring, decomposition, star system, unique colouring A M S C L A S S I F I C A T I O N 05B30; 05C51; 05C15 1 1  ∪ ⩽⩽ DARIJANI AND PIKE | 531 How to cite this article: Darijani I, Pike DA. Colourings of star systems. J Combin Des.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Originally, the problems in [4] and this paper were to be tools to work toward coloring star systems. For the most part, Darijani and Pike [1] have answered this question. We now hope these results can be used for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, the problems in [4] and this paper were to be tools to work toward coloring star systems. For the most part, Darijani and Pike [1] have answered this question. We now hope these results can be used for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this paper was inspired by coloring star systems investigated in [1]. Darijani and Pike colored e-stars systems of the complete graph.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Darijani and Pike [3] showed that for any integer k 2, there exists a k-chromatic 3-star system of order n for all sufficiently large admissible n. They also generalized this result for e-star systems for any e 3. They showed that for all k 2 and e 3, there exists a kchromatic e-star system of order n for all sufficiently large n such that n ≡ 0, 1 (mod 2e).…”
Section: Introductionmentioning
confidence: 87%
“…3 , w 1 , w 3 }, and Y = {v 2 , v 4 , w 2 }. Then B is a decomposition of K 4,3 into P 4 paths for which R and Y constitute an equitable 2-colouring.…”
mentioning
confidence: 99%